Performance evaluation of waste rock dump closure cover systems in different climate zones of Turkey - Baysal, BC; Yılmaz, KK (Mine Closure 2024: 17th International Conference on Mine Closure, 2024)
During the closure phase of mining operations, addressing the mining facilities containing hazardous substances is essential. To mitigate the environmental and health impacts of mine waste, an appropriate top cover system shall be implemented for those facilities. Regulatory standards for closure activities vary between countries. This study aims to assess the effectiveness of various cover system types, including the one outlined in the Turkish Mining Waste Regulation (TMWR), across different climate zones in Turkey, categorised according to the Köppen–Trewartha climate classification. Five distinct cover system types were simulated for each of the five climate zones in Turkey. The performance of these cover systems was evaluated based on their ability to prevent atmospheric water ingress under the cover where the mine waste is located. GeoStudio’s SEEP/W software was employed to conduct numerical seepage analyses, simulating the longterm (30 years) performance of various cover system types across different climatic conditions. The software provided water balance calculations upon completion of the model runs, allowing for a comparison of cover system performances based on net percolation rates in each study area. The results indicated that the TMWR type cover system achieved successful outcomes across all climate zones of Turkey. Additionally, simpler and more cost-effective cover systems, commonly used in specific climatic conditions worldwide, also demonstrated some successful results, with very low net percolation rates (<5%). These findings underscored the significant influence of climate on cover system performance. Moreover, the study highlighted the necessity of performing site-specific investigations, considering local meteorological conditions, specific design criteria, and parameters for each case. This approach is essential due to the unique hydroclimatic, hydrogeologic, and design characteristics of each study area.
Keywords: mine closure plan; closure cover system design; Turkish mining waste regulation; waste rock dump; numerical modelling